2020
DOI: 10.1371/journal.pone.0231350
|View full text |Cite
|
Sign up to set email alerts
|

Teach-back: A systematic review of implementation and impacts

Abstract: Patients often have difficulty comprehending or recalling information given to them by their healthcare providers. Use of 'teach-back' has been shown to improve patients' knowledge and self-care abilities, however there is little guidance for healthcare services seeking to embed teach-back in their setting. This review aims to synthesize evidence about the translation of teach-back into practice including mode of delivery, use of implementation strategies and effectiveness. We searched Ovid Medline, CINAHL, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 62 publications
2
103
0
Order By: Relevance
“…Have you been connecting with social groups? 35 (80) 9 (20) Are you considered higher risk due to a vulnerable condition? Vulnerable means > 60 years old, immunocompromised (weakened immune system due to certain conditions or medications), has lung disease (asthma or COPD), or has chronic health conditions (diabetes, heart disease, and hypertension).…”
Section: Included In Cycles 1-4 (N = 44)mentioning
confidence: 99%
See 1 more Smart Citation
“…Have you been connecting with social groups? 35 (80) 9 (20) Are you considered higher risk due to a vulnerable condition? Vulnerable means > 60 years old, immunocompromised (weakened immune system due to certain conditions or medications), has lung disease (asthma or COPD), or has chronic health conditions (diabetes, heart disease, and hypertension).…”
Section: Included In Cycles 1-4 (N = 44)mentioning
confidence: 99%
“…Have you talked to that person or anyone else about your wishes and preferences for end-of-life care? 16 (80) 4 (20) Note: N = 44, all cycles; N = 24, cycles 1-2; N = 20, cycles 3-4.…”
Section: Included In Cycles 1-4 (N = 44)mentioning
confidence: 99%
“…Finally, although clinicians and nurses involved in the study were trained in the use of the e-pathway, which is an essential implementation strategy when introducing a new intervention, training alone is not sufficient to effect ongoing change and uptake into clinical practice [ 38 ]. Successful implementation normally requires an implementation plan and a multifaceted approach that includes collaboration between stakeholders and health services, staff flexibility, and a culture receptive to change [ 39 ]. A recent implementation study identified five strategies which may contribute to the successful implementation of an electronic care pathway: a strong national policy context for the rationalization of processes and data collection of efficiency indicator targets; financial and organisational resources; multidisciplinary engagement; guidelines and documentation for the standardisation and implementation; and development of an implementation protocol based on national guidelines and clinical expertise [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The virtual training program was designed specifically for remote sessions and involved more than performing standard pump training over a video call. Structured training specifically tailored to remote learning included (1) practice of pump-related features while showing competency related to specific tasks with use of the t:simulatorÔ smartphone app, (2) standardized instruction and feedback using the teach-back method, [6][7][8] and (3) followup review with the pump trainer and health care providers. Key aspects of the newly designed virtual training program, including preparation, in-session, and follow-up visits, are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%